Social Climber melalui Foodstagramming di Coffee Shop Excelso - Hasana, Siti Alya; Damaiyanti, Varinia Pura (Prodi Sosiologi FISIP ULM, 2025)
The presence of a phenomenon of foodstagramming on Instagram attracts the attention of many users, including students who use it to show their luxurious lifestyle and higher social status. The aim of this research is to examine the phenomenon of social cliber through foodstagramming of coffee shop Excelso by studentsand how social media influences student behavior regarding food and social status. This research uses a qualitative approach with descriptive research type. Data collection techniques used participant observation, in-depth semi-structured interviews and documentation. The results of this research reveal that students show social climber behavior through foodstagramming making it a means to express lifestyle and social status. Students choose special photo angles and edit images to attract followers attention, focusing on luxury and social class existence. They prioritize the visual aesthetics of food rather than values such as praying before eating. Choosing a location like Excelso aims to gain social recognition on social media. Furthermore, what motivates students to carry out this activity is the influence of the environment and program celebrities. Using lifestyle and consumption theory, this research examines how students perform foodstagramming to form style and identity through Instagram. Apart from that, this research also highlights how foodstagramming becomes a means to display the symbolic value of food drinks in Excelso. It is important for students to avoid a lifestyle that is only aimed at being seen as part of the upper class. It would be better if pocket money was used for more useful activities and to think more rationally in every action.